STRATEGI KOMUNIKASI DINAS LINGKUNGAN HIDUP PEMERINTAH KABUPATEN DAIRI DALAM MENSOSIALISASI KEBERSIHAN DI PASAR SIDIKALANG - Ahmad Arya Ardhana; Zuhriah, Zuhriah (eScience Humanity Journal, 2024)
The issue of waste cannot be separated from behavior and lifestyle patterns. Increased activity in the market significantly affects the quantity of waste piles in the market environment. This research stems from the finding that a lot of litter is scattered around due to the lack of public awareness about cleanliness. The purpose of this study is to examine the form of awareness and the appropriate communication strategies used to promote cleanliness in the traditional Sidikalang market. The methodology used is descriptive qualitative. Research techniques were conducted through field studies, open interviews, and literature reviews. The communication strategy implemented to raise awareness is carried out simultaneously and continuously, involving all layers of society concerned with waste issues. The communication strategy of the Environmental Agency of the Dairi Regency Government in promoting cleanliness in the traditional Sidikalang market indicates that many traders and the surrounding community are still unaware of cleanliness and the reuse of market waste. There is a lack of environmentally friendly behavior in the market to create a clean and healthy market. Additionally, the government's role in addressing environmental cleanliness issues and providing adequate facilities is still insufficient. This is evidenced by the scattered litter and waste piles